Filtering Patriarchal Culture: The Path to Equality and Change - Alfiyani, Nur (Institut Agama Islam Negeri (IAIN) Manado, 2023)
The study illustrates women's struggles in achieving political participation in Yogyakarta, a region still deeply rooted in a strong patriarchal culture. It is clear that society's assumption that politics is exclusive to men, coupled with women's lack of political knowledge, poses a significant obstacle to women's involvement in politics. Although the government mandate emphasizes the need for women's representation in politics, the level of women's participation in Yogyakarta's political institutions remains low, especially regarding the decision-making process. The focus of this research is on the role played by Kinasih Women's Solidarity (SP) in helping women in DIY to overcome patriarchal barriers and increase their involvement in politics. Through various empowerment programs and political education initiatives, SP Kinasih supports women in understanding the intricacies of politics and strengthening their ability in political decision-making. However, these efforts often met resistance from local religious and community leaders. A case study of a woman named Ulil, despite not successfully securing a legislative position, managed to influence women's political perspectives by advocating for women's viewpoints in candidate selection. This study concludes the importance of increasing women's capacity through empowerment programs to represent women's interests in political decision-making and overcome the patriarchal culture that still exists in Yogyakarta's political structure.